Trends and risk factors of bloodborne occupational exposure among healthcare workers in a Chinese tertiary hospital (2012–2022) - Wang, Liyi; Gao, Bing; Li, Shentai; Guo, Tianyuan; Cao, Xuhua; Zhao, Mengsha; Wang, Yating; Liu, Yan (Frontiers in Public Health, 2025)
ObjectiveThis study aimed to evaluate the epidemiological characteristics and long-term trends of bloodborne occupational exposure (BOE) among healthcare workers (HCWs) in a tertiary hospital in China from 2012 to 2022 (11 years) and evaluate BOE-associated factors during COVID-19 pandemic.MethodsA total of 1,725 self-reported cases of BOE were analyzed. The study comprised: (1) Descriptive analysis of demographic and professional variables; (2) Trend analysis of exposure events by season, month, sex, age, professional role, department, exposure source and occupational factors; and (3) Logistic regression analysis, with BOEs during the COVID-19 pandemic as the dependent variable.ResultsBOEs were most prevalent among female, formally employed staff, nurses, 25-year-olds, those with 1–5 years of experience, and junior-title holders. High-risk settings included the neurosurgery department and wards; common exposure types were needlestick injuries (mostly to ungloved hands) and first-time exposures. Hepatitis B virus (HBV) was the primary exposure source, with most exposed individuals having a prior HBV vaccination history. Exposure frequency peaked in December and the fourth quarter of the year. (1) Longitudinal trends showed rising BOE incidence in December, spring, and among specific groups: females, 25-year-olds, hospital doctors (including postgraduate/doctoral trainees), nurses (including interns), and staff with 10–15 years of experience. Syphilis/suspected syphilis-related exposures also demonstrated an upward trend. (2) Logistic regression identified exposure month, occupation, length of service as independent factors associated with BOE during the COVID-19 pandemic (p<0.05).ConclusionTargeted prevention and control strategies that focus on high-risk personnel, clinical departments, and specific procedures are essential to reduce the incidence of BOE among healthcare workers. Particular attention is required during public health emergencies (e.g., the COVID-19 pandemic), especially in addressing the January exposure peak, protecting physicians and mid-career staff with 16–20 years of service, and establishing cross-institutional mechanisms for coordinated BOE reporting and follow-up of support staff, in order to further minimize occupational risks. In addition, preventive measures such as targeted training programs, simulation-based exercises, and routine monitoring of HBV immunization status should be systematically implemented for trainees and newly recruited personnel.